2013
DOI: 10.1021/bi400734e
|View full text |Cite
|
Sign up to set email alerts
|

Stable and Potent Analogues Derived from the Modification of the Dicarbonyl Moiety of Curcumin

Abstract: Curcumin has shown promising therapeutic utilities for many diseases, including cancer; however, its clinical application is severely limited because of its poor stability under physiological conditions. Here we find that curcumin also loses its activity instantaneously in a reducing environment. Curcumin can exist in solution as a tautomeric mixture of keto and enol forms, and the enol form was found to be responsible for the rapid degradation of the compound. To increase the stability of curcumin, several an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 45 publications
2
40
0
Order By: Relevance
“…Curcumin can exist as a tautomeric mixture of keto and enol forms in solutions, and the enol form was found to be responsible for the rapid degradation of the curcumin. Chakraborti et al., found that the stability of curcumin was improved when the central diketone moiety of the curcumin was replaced by isooxazole and pyrazole groups. Structural modifications of curcumin were proven to be a meaningful approach to discover analogues with enhanced properties .…”
Section: Methodsmentioning
confidence: 99%
“…Curcumin can exist as a tautomeric mixture of keto and enol forms in solutions, and the enol form was found to be responsible for the rapid degradation of the curcumin. Chakraborti et al., found that the stability of curcumin was improved when the central diketone moiety of the curcumin was replaced by isooxazole and pyrazole groups. Structural modifications of curcumin were proven to be a meaningful approach to discover analogues with enhanced properties .…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, compounds 2 and 3 also showed better free radical scavenging activity than curcumin ( Table 4). [58] Ahsan et al (2013) depicted synthesis, characterization and in vitro anticancer activity of a novel series of curcumin analogs to explore potential therapeutics for cancer. Several compounds were tested and showed promising anticancer activity in both onedose and 5-dose assays.…”
Section: Curcumin Pyrazole and Isoxazole Analogs As Anticancer Agentsmentioning
confidence: 99%
“…Curcumin is a naturally occurring phenol found in turmeric spice. A highly lipophilic molecule, curcumin exists in 1,3-diketo and two enol tautomers, and displays relatively low bioavailability due to degradation of the enol tautomer and rapid excretion from the body (133,134). Many strategies have been attempted to increase curcumin bioavailability, including nanoparticulate formulations, synthesis of curcumin analogues, co-treatment with piperine (a UDP-glucuronosyl transferase inhibitor), and packaging in micelles (133,(135)(136)(137)(138).…”
Section: Natural Compounds 521 Curcuminmentioning
confidence: 99%